Risk prediction of combined fibrinogen degradation products, thrombomodulin, and maximum amplitude for assessing association with venous thromboembolism in patients with post-traumatic fractures - Shaoli Huang; Xiaoyan Wang; Hongwu Xin; Xihe Zhang; Wenying Luo (PLoS ONE, 2026)
Background Venous thromboembolism (VTE) is a globally prevalent severe disease associated with high morbidity and mortality. Currently, thrombomodulin (TM), fibrinogen degradation product (FDP), thromboelastography have been the subject of several research pertaining to VTE; However, the combined diagnostic efficacy of these tests for VTE remains unclear. Therefore, we proposed to investigate the diagnostic efficacy of TM, FDP, thrombelastography in predicting VTE. Methods The patients with traumatic fracture included in the study were divided into a VTE group (n = 44) and a control group (n = 56) based on imaging diagnosis. Spearman correlation was employed to analyze the relationship between coagulation-related markers and thromboelastography indices. Variables were analyzed using multifactorial logistic stepwise regression. Statistically significant indicators were included in the receiver operating characteristic curve to evaluate their diagnostic efficacy for VTE. Results The VTE group showed significantly higher levels of multiple coagulation-related parameters and thromboelastography indices compared to the control group. Specifically, D-dimer levels were 8.87 (4.77, 15.07) mg/L in the VTE group versus 2.36 (1.07, 5.73) mg/L in the control group ( P < 0.001), and FDP levels were 36.45 (11.34, 73.75) μg/mL versus 7.96 (4.57, 12.73) μg/mL ( P < 0.001). TM levels were also elevated in the VTE group at 11.74 (9.26, 13.27) TU/mL compared to 8.60 (7.20, 11.60) TU/mL in controls ( P = 0.001). Among thromboelastography parameters, maximum amplitude (MA) was 72.06 ± 7.61 mm in the VTE group versus 67.03 ± 7.21 mm in controls ( P = 0.001), and clot intensity (G) was 13,259.75 (9,346.48, 18,545.83) d/sc versus 9,659.70 (8,009.33, 13,480.40) d/sc ( P = 0.004). Conversely, the blood clot formation rate was lower in the VTE group (1.25 [0.83, 1.40] vs. 1.30 [1.10, 1.58], P = 0.037). Linear correlation analysis revealed significant positive associations between platelet counts and both MA (r = 0.612, P < 0.001) and G (r = 0.588, P < 0.001). Multivariate logistic stepwise regression identified FDP (OR = 1.047, 95% CI: 1.025–1.070, P < 0.001), TM (OR = 1.215, 95% CI: 1.033–1.429, P = 0.019), and MA (OR = 1.104, 95% CI: 1.026–1.188, P = 0.008) as independent risk factors for VTE. ROC curve analysis demonstrated that the combined model of these three markers achieved the highest diagnostic efficacy, with an area under the curve (AUC) of 0.860 (95% CI: 0.789–0.931), sensitivity of 70.5%, and specificity of 85.7%. Conclusion Combined testing of FDP, TM, and MA holds clinical significance for clinicians to early predict the risk of VTE in post-traumatic fracture patients and implement preventive measures.